Peran Politik dalam Pembangunan Ekonomi Indonesia - Moh. Hudi (Universitas Islam Darul Ulum Lamongan, 2020)
Indonesia is a developing country which is one of the countries that are members of the group of world countries, including the World Trade Organization (WTO), the Asian Pacific Economic Corporation (APEC), Southeast Asia Association of South East Of Asian Nation (ASEAN) and others. Even though until now the Indonesian state in its level of economic development is not very well established. Even among ASEAN countries, Indonesia is still lagging behind other ASEAN countries. This will hamper Indonesia's growth in the medium and long term if the quality of the economy is not immediately improved.